Understanding patterns of rural decline: a numerical analysis among Kansas counties - Lachky, Stephen Thomas (Kansas State University, 2010)
Rural communities are a vital part of America; they account for two-thirds of the land in the U.S. and are home to about one in every nine Americans. Throughout history, our country has been shaped by their presence and social, economic, and cultural influence (Flora et al., 2004). For over the past half century however, communities in rural America have been declining in size and population; in nearly 70% of the counties of the Great Plains, there are fewer people residing there today than there were in 1950. Furthermore, over the last half of the 20th century, residents living on farms in America have dropped by two-thirds (Mayer, 1993). These statistics indicate a drastic pattern of population loss among small town communities and farms throughout rural America, which is devastating because they [towns] ultimately depend on population to contribute to their industries, businesses, and local services in order to function and survive (Wood, 2008). Understanding the causes of rural decline is important in the field of planning; nevertheless, identifying statistical relationships and spatial patterns associated with rural decline is just as important. This research report is both an overview on rural decline, and a comparative analysis of rural decline amongst Kansas counties. The objective of this research report is to identify characteristics, patterns, and trends associated with rural decline, and to rank Kansas counties according to a list of variables which represent those characteristics for analytical purposes. The ultimate goal is to explain any spatial phenomenon associated with the variables and Kansas counties, as well as identify specific counties in Kansas most devastated by factors associated with rural decline. In order to determine which counties are most devastated by factors associated with rural decline, a numerical comprehensive comparative analysis will be conducted; the results of the analysis will serve as a side-by-side measure of rural decline among Kansas counties. It will also serve as the template for conducting the simulation and modeling research; ArcGIS 9.3.1 will be utilized in order display the characteristics, patterns, and trends of rural decline spatially among Kansas counties. The final maps will help serve to derive final conclusions on rural decline in Kansas.
Keywords: Rural decline; Rural America; Small towns; Kansas counties; Comparative analysis; Numerical analysis; Urban and Regional Planning (0999)